2010
DOI: 10.1091/mbc.e10-02-0082
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Membrane Proteins Insert into the Endoplasmic Reticulum

Abstract: We demonstrate that the entry of peroxisomal membrane proteins (PMPs) into the ER is mediated by the general ER import machinery. Within the ER, PMPs attain their correct topology and subsequently travel to peroxisomes. Our results show that the ER forms an obligate requirement to maintain peroxisomes in multiplying cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
172
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(179 citation statements)
references
References 66 publications
4
172
3
Order By: Relevance
“…Also in yeast, recombinant Pex3p bearing an attached signal sequence and, therefore, unequivocally addressed to the ER, ends up integrated into peroxisomes (22). More recently, work on Saccaromyces reported ER targeting of 16 PMPs mediated by Sec61p and Get13, both in proliferating wild-type cells and in mutant cells lacking peroxisomes (48). This work also showed that PMPs leave the ER in a Pex3-Pex19p-dependent manner, implying a new functional role for Pex3p and Pex19p, i.e.…”
Section: Experiments In Yeast Involve the Endoplasmic Reticulum As Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in yeast, recombinant Pex3p bearing an attached signal sequence and, therefore, unequivocally addressed to the ER, ends up integrated into peroxisomes (22). More recently, work on Saccaromyces reported ER targeting of 16 PMPs mediated by Sec61p and Get13, both in proliferating wild-type cells and in mutant cells lacking peroxisomes (48). This work also showed that PMPs leave the ER in a Pex3-Pex19p-dependent manner, implying a new functional role for Pex3p and Pex19p, i.e.…”
Section: Experiments In Yeast Involve the Endoplasmic Reticulum As Thmentioning
confidence: 99%
“…An early study in rat liver using cell fractionation methods described data suggesting the presence of PMP50 and PMP36 in ER membrane fractions (51). Only very recently a targeting of a variety of PMPs to the ER has been reported in yeast (48). However, this is a previously unknown feature of ZS cells, which not only entails great interest regarding the role of the ER in peroxisomal biogenesis but also suggests a new role of Pex3p and Pex16p dealing with the traffic of PMPs from the ER to peroxisomes.…”
Section: The Er-to-peroxisome Pathway In Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) In cells with a defective GET pathway, Pex15 is mistargeted to the mitochondrial outer membrane and is removed from this compartment with the aid of the AAA-ATPase Msp1 (red arrows). Small amounts of Pex15 can be correctly delivered to peroxisomes (12), possibly by the alternative Pex19/Pex3 pathway.…”
mentioning
confidence: 99%
“…1A). The peroxin Pex15 is initially inserted into the ER via the GET pathway and then transferred to peroxisomes via vesicular transport (8,12,13). Other tailanchored proteins use an ER-independent pathway, where the precursors are targeted to peroxisomes via the Pex19 cytosolic chaperone and the peroxisome-resident receptor Pex3 (14).…”
mentioning
confidence: 99%